Effect of Cyclic AMP and Cyclic GMP on Thromboplastin (Factor III) Synthesis in Human Monocytes In Vitro - Lyberg, Torstein (Thrombosis and Haemostasis, 1983)
Human monocytes in vitro respond to various agents (immune complexes, lectins, endotoxin, the divalent ionophore A 23187, 12-0-tetradecanoyl-phorbol 13-acetate [TPA], purified protein derivative [PPD] of Bacille Calmette-Guerin) with an increased synthesis of the protein component of thromboplastin. The effect of cyclic AMP and cyclic GMP on this response has been studied. Dibutyryl-cyclic AMP, prostaglandin E1 and the phosphodiesterase inhibitors 3-butyl-1-methyl-xanthine (MIX) and rac -4-(3-butoxy-4-methoxybenzyl)-2-imidazolidinone (Ro 201724), separately and in combination have a pronounced inhibitory effect on the response to immune complexes and PPD, and a moderate effect on the response to endotoxin and lectins. The effect on TPA response and on the response to A 23187 was slight. Dibutyryl-cyclic GMP (1 mM) gave a slight inhibition of the TPA arid IC response, but had essentially no effect on the response to other inducers. The intracellular cAMP level increased when monocytes were incubated with IC, TPA or A 23187 followed by a decrease to basal levels within 1-2 hr, whereas lectin (PHA) and PPD did not induce such changes. The cAMP response to endotoxin varied. Stimulation with IC induced an increase in monocyte cGMP levels, whereas the other stimulants did not cause such changes.
Keywords: Cyclic AMP; Cyclic GMP; Thromboplastin; Monocytes; Phosphodiesterase inhibitors